Exploring the application of poly(1,2-ethanediol citrate)/polylactide nonwovens in cell culturing - Bandzerewicz, Aleksandra; Howis, Joanna; Wierzchowski, Kamil; Slouf, Miroslav; Hodan, Jiri; Denis, Piotr; Gołofit, Tomasz; Pilarek, Maciej; Gadomska-Gajadhur, Agnieszka (Frontiers in Bioengineering and Biotechnology, 2024)
Biomaterials containing citric acid as a building unit show potential for use as blood vessel and skin tissue substitutes. The success in commercializing implants containing a polymer matrix of poly(1,8octanediol citrate) provides a rationale for exploring polycitrates based on other diols. Changing the aliphatic chain length of the diol allows functional design strategies to control the implant's mechanical properties, degradation profile and surface energy. In the present work, poly(1,2ethanediol citrate) was synthesized and used as an additive to polylactide in the electrospinning process. It was established that the content of polycitrate greatly influences the nonwovens' properties: an equal mass ratio of polymers resulted in the best morphology. The obtained nonwovens were characterized by surface hydrophilicity, tensile strength, and thermal properties. L929 cell cultures were carried out on their surface. The materials obtained as part of the thesis were found to be non-cytotoxic and the degree of porosity was suitable for cell colonization. On the basis of the most important parameters for assessing the condition of cultured cells (cell density and viability, cell metabolic activity and lactate dehydrogenase activity), the potential of PLLA+PECit nonwovens for application in tissue engineering was established.